-41=1-6(x+6)

Simple and best practice solution for -41=1-6(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -41=1-6(x+6) equation:


Simplifying
-41 = 1 + -6(x + 6)

Reorder the terms:
-41 = 1 + -6(6 + x)
-41 = 1 + (6 * -6 + x * -6)
-41 = 1 + (-36 + -6x)

Combine like terms: 1 + -36 = -35
-41 = -35 + -6x

Solving
-41 = -35 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-41 + 6x = -35 + -6x + 6x

Combine like terms: -6x + 6x = 0
-41 + 6x = -35 + 0
-41 + 6x = -35

Add '41' to each side of the equation.
-41 + 41 + 6x = -35 + 41

Combine like terms: -41 + 41 = 0
0 + 6x = -35 + 41
6x = -35 + 41

Combine like terms: -35 + 41 = 6
6x = 6

Divide each side by '6'.
x = 1

Simplifying
x = 1

See similar equations:

| 7-2g=19 | | 3x+33y=-18 | | 18=-10 | | 5x-7=-10x+18 | | -0.6+-2.5= | | -0.6+-2.5= | | 3n-13=29 | | .6p=132.6 | | (25b-9)-8(3b+3)=-5 | | 6(x-7)=2(x+7) | | x*x-1=x | | 235+0.75y=125+1.63y | | 36xy-16y= | | 989=11u-(-120) | | 12+(-3x)=3 | | .8w+.4w+.1w=4 | | -10(1.5)+10y=-100 | | 1-ax*2x+1= | | 3m-5=-8(6+5n) | | 2x+33= | | 40=8d | | 3(r-4)=19 | | 3x+5y=-58 | | -3(4p+6)-2(1-14p)=3(3+5p) | | 12+(-3*2)= | | 3z-7=5a+33 | | 9[5-3(x+2)]= | | (1-ax)*(2x+1)= | | 5x+8-12x+6= | | 6n+4=3n+12 | | -15+5z=2+1 | | 17r+8=42 |

Equations solver categories